Employee Engagement Terhadap Employee Performance (Sebuah Studi Literatur) - Tedy Ardiansyah (Sosio e-Kons, 2020)
A literature review is to form a meta-analysis or theoretical construct in finding the truth of the research. The purpose of this study is to determine the comparison of the journal literature review which will later form an appropriate literature model. The general method implemented in this research is qualitative research where the approach is carried out through literature studies, namely research that critically examines knowledge, ideas, or findings, and provides theoretical and methodological contributions to the object of study. The results of this study indicate an inventive placement of the appropriate variable positions for Employee Engagement to form an appropriate research result model as reference material and to determine the dominance of journal reference types, for human resource studies including sample data, types of research and business or business activities.